(untitled) (Journal Of Educational and Psychological Researches, 2022)
The present study aims to develop and apply the unrealistic optimism scale among high school students. The researcher has designed a scale of (38) paragraphs to measure the unrealistic optimism. A sample of (200) male and female students were chosen randomly to collect the needed data. The study found that the unrealistic scale of optimism has good psychometric characteristics. The research sample has a high level of التفاؤل غير الواقعي لدى عينة البحث unrealistic optimism. There is a statistically significant difference between male and female in the unrealistic optimism in favor of the male students. Finally, there is a statistically significant difference between students in the fourth and sixth grades. الاعدادي , وقد أوصت الدراسة ا مكانية استخدام ال مقياس من قبل المرشدين التربويين في تشخيص The study suggested اجراء دراسة مماثلة على طلبة المرحلة المتوسطة ومقارنة نتائجه ا مع نتائج الدراسة الحالية a similar study taking up middle school students and comparing its results with the results of the current study.